The Transmission of Information in Chinese Folk Religion: Reflections on Fieldwork in Putian, Fujian*. (May 2019) - Wu, Chongqing
In folk religion, the key to interaction among gods, ghosts, and people lies in the transmission of information. The separation between the spheres of yin and yang leads to an asymmetry of information and the need for communication. The transmission of information between ghosts and the living displays a differential mode of association 差序格局 in interpersonal relations. Two important means for this transmission are block divination 卜杯 and the spirit mediums known as tongji 童乩. The choice determines the mode of interaction between humans and spirits, the specific role played by gods, and the type of information they provide. That information may be called "sacred knowledge, " which contrasts with ordinary social knowledge in the characteristics, mechanisms, and rules regarding its transmission.